Trade and Industrial Policy of Transition Economies - José Luis Moraga Gonzales; Jean-Marie Viaene (Center for Economic Studies and ifo Institute (CESifo), 2001)
Trade reforms in transition economies are analyzed in a model of trade and vertical product differentiation. We first show that trade liberalization in transition economies reduces the local firm's output and raises the prices of all variants. Second, we find that neither free trade nor the absence of a subsidy are optimal. Third, there exists a rationale for a government commitment to use socially optimal trade and industrial policies to release the domestic firm from low-quality production. Finally, we establish an equivalence result between the effects of exchange rate changes and those of trade policy on price competition (but not on social welfare).
Keywords: 330; Exchange rates; leapfrogging; optimal trade policy; product quality; trade liberalization